Sintering of undoped SnO2 - Leite, E. R.; Cerri, J. A.; Longo, E.; Varela, J. A. (Associação Brasileira de Cerâmica, 2003)
Pure SnO2 sintering was studied by constant heating rate and isothermal sintering. The constant heating rate study showed no macroscopic shrinkage during the sintering process up to 1500 ºC. Pore size distribution measurements, using gas desorption, and grain size and crystallite size measurements of isothermally sintered samples showed no formation of non-densifying microstructures during the sintering process. These results are a strong indication that densification was prevented by thermodynamic factors, mainly the high ratio of gammaGB/gSV. An explanation, based on the nature of covalent bonding and the balance between attractive and repulsive forces, was proposed to explain the high gammaGB/gammaSV ratio in SnO2.

A sinterização de SnO2 puro foi estudado por taxa constante de aquecimento e por sinterização isotérmica. O estudo de taxa constante de aquecimento mostrou que não ocorre retração macroscópica durante o processo de sinterização até temperaturas de 1500 ºC. Medidas de distribuição de tamanho de poros, usando adsorção de gás, tamanho de grão e tamanho de cristalito para amostras sinterizadas isotermicamente mostrou a não formação de uma microestrutura não-densificante durante o processo de sinterização. Estes resultados são um forte indicativo que a densificação foi inibida por fatores termodinâmicos, principalmente o alto valor da razão de gamaGB/gSV. Uma explicação, baseada na natureza covalente da ligação química e no balanço entre forças atrativas e repulsivas, é apresentada para explicar o alto valor da razão gamaGB/gamaSV no SnO2.
Sinterização de SnO2 não dopado
Keywords: sintering; SnO2; microstructure; sinterização; SnO2; microestrutura